Vivienne Westwood - Westwood, Vivienne 1941-2022; Kelly, Ian 1966- (Picador, 2014)
Vivienne Westwood is one of the icons of our age; fashion designer, activist, co-creator of punk, global brand and grandmother; a true living legend. Both her name and brand are recognised the world over, whilst at home in the UK she has attained National Treasure status as the nation's favourite fearless female icon. This is her story. Told for the first time in all its glamour and glory and with her unique voice, unexpected perspective and passionate honesty: 'The living deserve respect. The dead deserve the truth; Ian and I are working together on this and I am excited that this will be my story, the story nobody ever did before.' For the first and only time, she is both writing and collaborating on a unique personal memoir and authorised biography: partly her own voice, partly through contributions from her vast network of friends, family and associates. Ian Kelly (award-winning biographer of, amongst others, fashion maverick Beau Brummell and the original self-publicist, Giacomo Casanova) brings the insights of a historian and friend of Vivienne to the life and works of one of the major influences of our age in this wonderful, insightful collaboration
Includes bibliographical references (pages 433-437) and index
Keywords: Westwood, Vivienne / 1941-; Westwood, Vivienne; Westwood, Vivienne -- 1941-2022; Women fashion designers; Women fashion designers / Great Britain / Biography; Fashion designers / Great Britain / Biography; Mode; Design; England / London; Großbritannien; Autobiografie